THE IMPLEMENTATION OF INTEGRATIVE MODEL OF TEXT-BASED FOLKTALE WRITING LEARNING TO IMPROVE CREATIVE AND INDEPENDENT VIRTUES OF JUNIOR HIGH SCHOOL STUDENTS (The Journal of Educational Development, 2014)
Three purposes of this study are: 1) to identify the characteristics of integrative model of text-based foktale writing learning for SMP students; 2) to develop an integrative model of text-based folktale writing learning SMP students; and 3) to describe the acceptability of integrative model of text-based folktale writing learning based on the result of field trial. This study employs research and development approach. The study results in an invention of characteristic theory of development model in form of seven unique learning procedures for folktale writing. The result of research is a learning set of development model. The acceptability is based on the comparisson test, regression test, and the following observations: the average number of studentsâ€™ achievement development which is 19.17; the effect of creative behavior (X1) 70.92%; independence (X2) 84.1%; and the impact of X1 dan X2 86.62%. The average score of teachersâ€™ observation 4.3 (high), and the answer â€œyesâ€obtained from studentsâ€™ observation is 94.53%. Based on the trial, the use text-based integrative model is concluded to obtain high acceptability because it manages to improve the procces and the result of learning.